Forgery and memory at the end of the first millennium - Roach, Levi, 1985- (Princeton University Press, 2021)
An in-depth exploration of documentary forgery at the turn of the first millennium Forgery and Memory at the End of the First Millennium takes a fresh look at documentary forgery and historical memory in the Middle Ages. In the tenth and eleventh centuries, religious houses across Europe began falsifying texts and improving local documentary records on an unprecedented scale, often for the first time. As Levi Roach illustrates, the resulting wave of forgery signaled major shifts in society and political culture, shifts which would lay the foundations for the European ancien régime.Spanning documentary traditions across France, England, Germany and northern Italy, Roach examines five sets of falsified texts to demonstrate how forged records produced in this period gave voice to new collective identities, within and beyond the Church. Above all, he demonstrates how this fad for falsification points to new attitudes toward past and present--a developing fascination with the signs of antiquity. These conclusions revise traditional master narratives about the development of antiquarianism in the modern era, showing that medieval forgers were every bit as sophisticated as their Renaissance successors. Medieval forgers were simply interested in different subjects--the history of the Church and their local realms, rather than the literary world of classical antiquity. A comparative history of falsified records at a crucial turning point in the Middle Ages, Forgery and Memory at the End of the First Millennium offers valuable insights into how institutions and individuals rewrote and reimagined the past.